First Characterization of Chicken Interleukin-9 - He, Shuangjiang; Chen, Lina; Hao, Xiaoli; Yang, Yi; Shang, Shaobin (Frontiers in Immunology, 2022)
Interleukin-9 (IL-9) is a pleiotropic cytokine that acts on a variety of cells and tissues, and plays roles in inflammation and infection as well as tumor immunity. While mammalian IL-9s have been widely investigated, avian IL-9 has not yet been identified and characterized. In this study, we cloned chicken IL-9 (chIL-9) and performed a phylogenetic analysis, examined its tissue distribution, characterized the biological functions of recombinant chIL-9 (rchIL-9) and the expression form of natural chIL-9. Phylogenetic analysis showed that chIL-9 has less than 30% amino acid identity with mammalian IL-9s. The chIL-9 mRNA can be abundantly detected only in the testis and thymus, and are significantly up-regulated in peripheral blood mononuclear cells (PBMCs) upon mitogen stimulation. The rchIL-9 was produced by prokaryotic and eukaryotic expression systems and showed biological activity in activating monocytes/macrophages to produce inflammatory cytokines and promoting the proliferation of CD3+ T cells. In addition, four monoclonal antibodies (mAbs) and rabbit polyclonal antibody (pAb) against rchIL-9 were generated. Using anti-chIL-9 mAbs and pAb, natural chIL-9 expressed by the activated PBMCs of chickens with a molecular weight of 25kD was identified by Western-blotting. Collectively, our study reveals for the first time the presence of functional IL-9 in birds and lays the ground for further investigating the roles of chIL-9 in diseases and immunity.